Self-directed learning skills for ODeL students in crisis situations: lessons from Zimbabwe Open University during Covid-19 - Magwa, Logic; Zongozzi, Johannes Nkosinathi (Frontiers in Education, 2026)
This study explores self-directed learning skills utilized by students at Zimbabwe Open University, Masvingo regional campus during the Covid-19 pandemic with the aim of identifying context-specific skills that can prepare ODeL students for future crisis situations. While ODeL institutions are often assumed to be resilient to disruptions, the Covid-19 pandemic exposed significant gaps in students’ preparedness for autonomous learning in crisis contexts. In this qualitative case study, data were generated through semi- structured interviews with seven (7) purposefully selected lecturers and a quality assurance coordinator. Additionally, one focus group discussion session with seven (7) students was conducted. Guided by self-directed learning theory and informed by the community of inquiry (CoI) framework, the study found that self-management and personal discipline, cognitive and analytical skills and communication and technological proficiency were critical for sustaining learning during the crisis. The unique contribution of this study lies in its empirical identification of self-directed learning skills enacted by ODeL students specifically during a crisis context, an area that remains underexplored in SDL scholarship. The study recommends integrating SDL explicitly into teacher education and ODeL curricula to enhance preparedness for future disruptions